2013
DOI: 10.1021/ef4014423
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Correlations for Estimating Product Yields from Delayed Coking

Abstract: The objective of this paper is to compare the prediction capability of different correlations for calculating delayed coking yields. The evaluation was developed taking operation data reported in the literature into account for delayed coking commercial plants. The effects of pressure, feed type, and temperature on product yields were analyzed. Correlations that include the effect of operating conditions proved to be more accurate compared to those that consider only feed properties. From the calculation of yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…Second, the hydrotreated residue oil from the RHT unit was fed into the coking reactor at a rate of 1 g/min; before which, the residue oil was mixed with a flow of 100 mL/min N 2 gas. The nitrogen pressure is approximately 0.15 MPa, which is similar to that in the industrial delayed coking process. , After coking, the cracking oil was cooled in a separator with a water-cooling system. The coke and liquid products were collected to determine the yields of coke and liquid products.…”
Section: Experimental Sectionmentioning
confidence: 82%
See 1 more Smart Citation
“…Second, the hydrotreated residue oil from the RHT unit was fed into the coking reactor at a rate of 1 g/min; before which, the residue oil was mixed with a flow of 100 mL/min N 2 gas. The nitrogen pressure is approximately 0.15 MPa, which is similar to that in the industrial delayed coking process. , After coking, the cracking oil was cooled in a separator with a water-cooling system. The coke and liquid products were collected to determine the yields of coke and liquid products.…”
Section: Experimental Sectionmentioning
confidence: 82%
“…Through correlating the feedstock properties and the product distributions of DC units, it was found that the coke yield linearly depends on the content of Conradson carbon residue (CCR) in the feedstocks with the slope varying from 1.2 to 1.66. , Furthermore, Khorasheh et al found that increasing the operation temperature or decreasing the reaction pressure of the DC units could enhance the yield of high-value liquid products and meanwhile reduce coke production but imposed little effect on the sulfur content of coke and the content was still much higher than 3.0 wt % . Hence, in order to reduce the coke yield and the sulfur content in coke at the same time, it seems insufficient to only modify the DC operation conditions and a pretreatment process of the feedstocks before the DC process should be needed.…”
Section: Introductionmentioning
confidence: 99%
“…The hightemperature reaction vapors are introduced into the fractionator from the coke drum, application to a delayed coking unit where light fractions are recovered (Sawarkar et al, 2007;Muñoz et al, 2013). The feedstock (VR) is introduced directly to the bottom of the fractionator, where it is preheated, lighter fractions are removed as sidestreams, and the fractionator bottom stream is heated in a furnace to reach quickly the thermal cracking temperature.…”
Section: Process Descriptionmentioning
confidence: 99%
“…Thus, characterize it adequately is a complex task, making complicated the modeling of coking reactions and the obtaining of a detailed kinetic model (Muñoz et al, 2013). Thus, characterize it adequately is a complex task, making complicated the modeling of coking reactions and the obtaining of a detailed kinetic model (Muñoz et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These models provide an estimate of the yield of coke, liquids, and gases and are based on the assumption that the process is at steady state. An interesting comparison of these correlation models for delayed coking simulation can be found in Ancheyta et al (2013). After a validation with experimental data, they concluded that the correlation of Volk, Wisecarver & Sheppard (2002) provided the higher accurate results as it takes into account not only the properties of the feed but the operating conditions as well.…”
Section: Introductionmentioning
confidence: 99%